Influence of the timing of exit from feedlot on the conception rate and pregnancy loss of Nelore heifers, aged 12 to 16 months, subjected to a FTAI program - Carvalho, Juliany Sá de (2025)
The reproductive performance of precocious Nelore heifers, aged 12 to 16 months, exposed to successive timed artificial insemination (TAI) programs and subjected to different periods of feedlot exit after the first TAI (TAI1) was evaluated. A total of 1,536 heifers from two commercial farms (Farm 1; n=840 and Farm 2; n=696) were used in the study. The heifers were confined immediately after weaning, at 210 to 240 days of age, and subjected to successive TAI protocols during the breeding season (BS). The date of TAI1 was considered the beginning of the BS (D0). Five days after TAI1 (D5), the heifers were block-randomized by weight into two groups: G5 (n=790), heifers that were transferred from feedlot to pasture at D5, and G30 (n=746), heifers that remained confined for up to 30 days after TAI1. Pregnancy diagnoses were performed on D30 and D60 (PD30 and PD60, respectively). Immediately after PD30, the heifers in G30 were transferred from feedlot to pasture. At this point, the females from both groups were re- grouped, maintained on the same pastures, and subjected to the same management until the end of the BS. Average daily gain (ADG) was evaluated between the intervals from D-9 to D30 (ADG_-9_30) and from D30 to D60 (ADG_30_60). The variables were analyzed using the PROC MIXED and GLIMMIX procedures in SAS 9.4. No differences were observed between the treatments for weights at D-9 (G5=335.6 and G30=336.1 kg; P=0.95) and final PD (G5=376.3 and G30=377.7 kg; P=0.43). The weights at PD30 and PD60 differed (P<0.001) between the treatments (G5=338.9 and 346.3 kg; G30=360.2 and 354.0 kg, respectively). ADG_-9_30 and ADG_30_60 showed significant differences (P<0.001 and P=0.03, respectively) between the treatments (G5=0.082 and G30=0.594 kg; G5=0.156 and G30=-0.271 kg, respectively). No interaction effect (P>0.05) between the treatments and farms was found regarding conception rates at 30 days for different services, nor for the final pregnancy rate. Even after PD60, no differences (P=0.32) were detected between treatments (G5=44.6% and G30=46.1%). The pregnancy loss rate between PD30 and PD60 (PL_30_60) was 7.6% and 8.0% for G5 and G30, respectively (P=0.50). At the end of the BS, similar final pregnancy rates were found between the treatments (G5=78.6% and G30=81.1%; P=0.97). In conclusion, moving precocious Nelore heifers from feedlot to pasture five days after TAI1 does not result in reduced reproductive efficiency.